Das Imperium Romanum und seine Gegenwelten Die geographisch-ethnographischen Exkurse in den Res Gestae des Ammianus Marcellinus - Vergin, Wiebke (Millennium-Studien / Millennium Studies, 2012)
Ammianus is regarded as the greatest historian of late antiquity. Yet his geographic and ethnographic digressions were long underestimated as examples offeigned eruditionand as undue interruptions to the historical narrative. The author of this volume believes that the key to understanding Ammianus`s work as a whole lies in his teaching of classical rhetoric, his metaphoric reading of landscapes, and the creation of spaces for memory and counterworlds to the Imperium Romanum. In this way, historical understanding and digressions concerning geographic knowledge must be viewed as interdependent features of the text. The author thus casts a new light on Ammianus`s literary achievements.